Evaluation of news communication effect based on cognitive neuroscience - Chen Xiaozhu (De Gruyter, 2019)
Based on the development of cognitive neuroscience and communication science at home and abroad, this study introduces the application of cognitive neuroscience experiments in communication researches at home and abroad, including the research and application of communication effects in advertising, picture, video, web design and animation culture. This study discusses the important significance of relevant frontier achievements to the development of news communication science. The rise of cognitive neuroscience provides a new perspective for understanding the psychological cognitive mechanism of the audience and optimizing the communication effect of service media. On the basis of introducing the status quo of cognitive neuroscience in audience rating evaluation of news broadcast, this study introduces the advantages and functions of this method in audience rating evaluation of news broadcast with eye movement experiment as an example, which provides a new method and empirical case for seeking audience rating evaluation of news broadcast.